A Novel Design of Aperiodic Arrays for Ultrawideband Beam Scanning and Full Polarization Reconfiguration - Zhang, Ziyu; Liu, Jia; Su, Jianxun; Song, Jiming (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this letter, a multifunction aperture array is proposed for ultrawideband (UWB) scanning and polarization reconfiguration. The UWB array consisted of linearly polarized elements is capable of operating in four polarization modes (+45° linear polarization (LP), -45° linear polarization, left-hand circular polarization (LHCP) and right-hand circular polarization (RHCP)). This work involves two essential techniques: (a) A new beam-scanning UWB array synthesis approach. An iterative convex optimization strategy is utilized to determine the element locations and obtain the minimum sidelobe level (SLL) for multiple patterns. (b) The polarization reconfigurable technique for beam-scannable arrays. In this part, a sequential rotation and excitation compensation (SR-EC) technique provides polarization reconfiguration for a beam-scannable array consisting of linearly polarized elements. A beam-scanning UWB array is designed by using the proposed UWB array synthesis approach and the SR-EC polarization reconfigurable technique. The Feko numerical result shows 0°-60° beam peak steering, a 4:1 bandwidth (1-4 GHz), and fourpolarization reconfigurability.